1975
DOI: 10.1161/01.res.36.6.771
|View full text |Cite
|
Sign up to set email alerts
|

Reduced myocardial reflow and increased coronary vascular resistance following prolonged myocardial ischemia in the dog.

Abstract: Studies were performed to determine whether an alteration in coronary vascular resistance and a reduction in the reflow phenomenon occurred in the blood-perfused, heparinized canine heart after various periods of myocaridal ischemia. Regional myocardial blood flow was measured with radioactive microspheres. Proximal left anterior descending coronary artery blood flow was measured with a periarterial flow transducer. Reduced reflow to the ischemic portion of the left ventricle and increased resistance in the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
4
1

Year Published

1976
1976
2000
2000

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(45 citation statements)
references
References 17 publications
3
37
4
1
Order By: Relevance
“…First, the decrement in in vivo glycoside binding is almost certainly related in part to reduced regional blood flow to ischemic tissue. Alterations in cardiac glycoside uptake with administration after reperfusion might still result from persistent reductions in regional flow due to the no reflow phenomenon, previously demonstrated after similar periods of experimental coronary occlusion (21,22). Second, impaired digoxin binding could result from ischemia-induced alterations in the local milieu preventing optimum binding of the glycoside.…”
Section: Discussionmentioning
confidence: 95%
“…First, the decrement in in vivo glycoside binding is almost certainly related in part to reduced regional blood flow to ischemic tissue. Alterations in cardiac glycoside uptake with administration after reperfusion might still result from persistent reductions in regional flow due to the no reflow phenomenon, previously demonstrated after similar periods of experimental coronary occlusion (21,22). Second, impaired digoxin binding could result from ischemia-induced alterations in the local milieu preventing optimum binding of the glycoside.…”
Section: Discussionmentioning
confidence: 95%
“…The severity of the no-reflow phenomenon in myocardial tissue depends on the duration of occlusion. 28 Willerson et al 29 showed a significant decrease in reflow at 2 hours compared with reperfusion after 10 minutes of occlusion. This study indicates that the amount of early reflow is not critical in determining the severity of myocardial hemorrhage, and only small quantities are needed to create the phenomenon.…”
Section: Discussionmentioning
confidence: 97%
“…Myocardial ischemia/reperfusion cause coronary vascular injury as well as myocardial injury (20)(21)(22)(23)(24). Although the mechanism by which coronary vascular damage from myocardial ischemia/reperfusion occurs remains unclear, endothelial injury caused by the activated neutrophils has been shown to play an important role in this process (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%